ÁCIDO LINOLEICO CONJUGADO (CLA) E EXERCÍCIO FÍSICO: EFEITOS NA COMPOSIÇÃO CORPORAL - Juliane Barroso Leal; Gustavo Bernardes Fanaro; Vanessa Fernandes Coutinho (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Conjugated linoleic acid (CLA) has been evaluated as regards the safety of the use isolated, its administration, in liquid form or capsules, or as food ingredient in addition to various foods and on several occasions. The objective was to conduct a literature review, critically, about the origin, functional and physiological properties of CLA and its association with physical exercise in order to outline the deficiencies in existing studies and clarify their actual and/or potential actions in body composition. For this, a revision of the literature was conducted, no date restriction and only with primary sources. Studies show that CLA comprises a group of 56 geometric isomers of linoleic acid where the double bonds are generally positioned on carbon atoms 9 and 11, or 10 and 12 with combinations of cis and trans. The use of different methods for assessing body composition may contribute negatively to the comparison between studies, although not yet know the mechanism by which this occurs, studies show that there is an increase in energy expenditure through physical exercise, increased oxidation of fatty acids, reduction of energy intake and inhibition of enzymes involved in fatty acid metabolism and lipogenesis. It is necessary to develop further research which, among other things, assess the necessary recommendation, so that they can be used safely and effectively in the requirements related to improving body composition and how antiobesity agent.